Resistividade elétrica de cerâmicas de alumina a temperatura ambiente e a 600oC - Kawasaki, Jorge Massato (1992)
Alumina (Al2O3) ceramic specimens have been prepared via traditional ceramic process, namely, powder analyses, classification and conditioning, uniaxial cold pressong and sintering. DC electrical resistivity measurements has been carried out at RT and 600oC. A tubular resistive furnace with an alumina sample chamber with platinum leads and electrodes was used. The main results show that the electrical resistivity of polycrystalline alumina increases with the decrease of the porosity, having as a limit the single crystal resistivity. Moreover, the electrical resistivity depends on the average grain size in the 4Wm 10 Wm range. For grain sizes smaller than 4 Wm the porosity is found to be higher than 0,1%.